Exploration and Identification of Lichen in the Temon, Depok, and Tegalrejo - Hafizh Adyatma; Anna Rakhmawati; Bernadetta Octavia (Department of Biology Education FMIPA Universitas Negeri Yogyakarta in collaboration with Perhimpunan Biologi Indonesia, 2025)
This research aims to identify the diversity of lichen species in three different areas: Temon, Kulon Progo; Depok, Sleman; and Tegalrejo, Magelang. Besides that to analyze their ecological role as environmental bioindicators. The method used was direct field observation with visual documentation using a mobile phone camera, followed by morphological identification. The results of the study successfully identified nine lichen species: Flavoparmelia caperata, Physcia atrostriata, Dirinaria applanata, Phlyctis argena, Acarospora socialis, Ropalospora viridis, Pyxine sorediata, Cryptothecia striata, and Graphis sp.. These species exhibited unique adaptations to various substrates (tree bark, rocks, and urban environments) and showed sensitivity to environmental changes, particularly air pollution. The mutualistic symbiosis between fungi and photobionts (algae/cyanobacteria) is key to the resilience of lichens in marginal habitats. These findings strengthen the potential of lichens as natural bioindicators and ecological pioneers, while also highlighting the need for further research to map the distribution and applications of lichens in Indonesia.